Suggesting global insights to local challenges: expanding financing of rehabilitation services in low and middle-income countries - Bachani, Abdulgafoor M.; Bentley, Jacob A.; Kautsar, Hunied; Neill, Rachel; Trujillo, Antonio J. (Frontiers in Rehabilitation Sciences, 2024)
Purpose: Following the rapid transition to non-communicable diseases, increases in injury, and subsequent disability, the world-especially low and middle-income countries (LMICs)remains ill-equipped for increased demand for rehabilitative services and assistive technology. This scoping review explores rehabilitation financing models used throughout the world and identifies "state of the art" rehabilitation financing strategies to identify opportunities and challenges to expand financing of rehabilitation.We searched peer-reviewed and grey literature for articles containing information on rehabilitation financing in both LMICs and high-income countries. Results: Forty-two articles were included, highlighting various rehabilitation financing mechanism which involves user fees and other innovative payment as bundled or pooled schemes. Few studies explore policy options to increase investment in the supply of services.this paper highlights opportunities to expand rehabilitation services, namely through promotion of private investment, improvement in provider reimbursement mechanism as well as expanding educational grants to bolster labor supply incentive, and the investment in public and private insurance schemes. Mechanisms of reimbursement are frequently based on global budget and salary which are helpful to control cost escalation but represent important barriers to expand supply and quality of services.